1998
DOI: 10.1126/science.279.5355.1347
|View full text |Cite
|
Sign up to set email alerts
|

An Area Specialized for Spatial Working Memory in Human Frontal Cortex

Abstract: Working memory is the process of maintaining an active representation of information so that it is available for use. In monkeys, a prefrontal cortical region important for spatial working memory lies in and around the principal sulcus, but in humans the location, and even the existence, of a region for spatial working memory is in dispute. By using functional magnetic resonance imaging in humans, an area in the superior frontal sulcus was identified that is specialized for spatial working memory. This area is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

67
526
8
14

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 858 publications
(615 citation statements)
references
References 31 publications
67
526
8
14
Order By: Relevance
“…This is exactly what has been reported now several times in unit recordings in the PFC of monkeys [5][6][7]28,33,39]. A few event-related fMRI studies have varied the length of the retention delay up to 24 s and have reported that the DLPFC activity does indeed span the entire delay [34 -37].…”
Section: Memory Load Effectssupporting
confidence: 77%
See 1 more Smart Citation
“…This is exactly what has been reported now several times in unit recordings in the PFC of monkeys [5][6][7]28,33,39]. A few event-related fMRI studies have varied the length of the retention delay up to 24 s and have reported that the DLPFC activity does indeed span the entire delay [34 -37].…”
Section: Memory Load Effectssupporting
confidence: 77%
“…Positional information might be represented in oculomotor coordinates, where the memorized location is maintained in terms of a saccade vector that acquires the target. Therefore, rehearsal of locations could simply be reactivations of oculomotor programs without actually making overt eye movements and can account for consistent activation of the frontal eye-fields (FEF) during spatial working memory tasks [33]. Clear segregations by the type of rehearsal strategy exist in the frontal cortex [59].…”
Section: Rehearsal Processesmentioning
confidence: 99%
“…This suggests that these DLPFC maps cannot be strongly activated by merely remembering a location; instead, they are interested in both location and content. In contrast, the pre-FEF, an area that has been shown to be specialized for spatial working memory (Courtney et al, 1998), displayed robust map activity (and contralateral preference) in our saccade mapping experiments (Hagler et al, in preparation); whereas with the 2-back identity task, the contralateral preference is largely confined to the FEF (Fig. 3).…”
Section: Discussionmentioning
confidence: 68%
“…In a third study, Thompson-Schill et al (1997) found that activation within the left inferior frontal gyrus increased whenever subjects performed a task that required them to retrieve only some facts about an item while ignoring others. In addition, a number of fMRI studies have identified regions within the frontal lobe that are active when subjects must hold faces (Courtney et al, 1997;Cohen et al, 1997) or locations (Courtney et al, 1998; but see Owen et al, 1998) in working memory. In all these studies, there is a common theme: Frontal activation does not correspond to memory recall per se, but to mechanisms that guide memory recall, such as choosing one memory over another or holding a memory available for imminent use.…”
Section: The Frontal Lobesmentioning
confidence: 99%